An experimental and numerical study on the age depended bond-slip behavior between nano-silica modified carbon fibers and cementitious matrices. (April 2022) - Li, Huanyu; Zhao, Dong; Liebscher, Marco; Yin, Bo; Yang, Jian; Kaliske, Michael; Mechtcherine, Viktor
Abstract: Electrophoretic deposition of nano-silica on the surfaces of carbon fibers (CF) is a novel approach for modifying the interfacial bond properties between the fibers and cementitious matrices. To understand its pullout behavior with increasing age, single fiber pullout tests and scanning electron microscopy were performed at various curing times for pristine and modified fibers. In this article, a new approach for calculating the debonding energy is introduced and two theoretical models – a stress-controlled and an energy-controlled – were employed to obtain the critical interface failure criterion. The results showed that interfacial adhesion at fiber-matrix interface was increasingly improved with age compared to the untreated fiber, due to the formation of C–S–H gel in the vicinity of the fiber surface. Meanwhile, the untreated fibers exhibited only a slightly increasing trend of interfacial bonding with longer curing time. A finite element model was applied to simulate the fiber pullout failure, which incorporated a discrete cohesive concept into the smeared phase-field method in a Representative Crack Element (RCE) framework. Using a phenomenologically defined cohesive traction-separation law, the numerical simulations successfully captured the characteristics of the experimental pullout curves. According to proper parametric calibrations, good agreement was obtained between the numerical results and the respective experimental evaluations.